Gender-Based Discrimination in "Tears of the Giraffe" by Alexander McCall Smith: A Qualitative Analysis - Aflakha (Morphosis: Journal of Literature, 2024)
The aim of this study was to analyze the issue of gender-based discrimination in the novel Tears of the Giraffe by Alexander McCall Smith (2022). The novel portrays female characters who have been humiliated in the social environment. The data was analyzed through words and quotations by Judith Butler (1999) on gender performativity. This study used qualitative methods to analyze and reveal the situation of gender-based discrimination that is enforced by society, particularly against females. The results of this study showed distinct differences in the roles assigned to females and males. Roles and attributes are categorized differently based on what is considered appropriate for both genders. By making female characters the second gender, the novel represents gender-based discrimination against females where their roles are unfavorable in the house, workplace, and social life. Moreover, This study showed the struggle of females as a response to facing gender-based discrimination by breaking the stereotype of females as body owners and the second gender. Keywords: female, gender-based discrimination, male, stereotype